Bewertung von Medikamenten in der Geriatrie mit der neuen FORTA-Klassifikation: vorläufige klinische Erfahrung = Assessment of drug treatment in geriatrics with the new FORTA criteria : preliminary clinical experience - Frohnhofen, Helmut; Michalek, Carina; Wehling, Martin (Deutsche medizinische Wochenschrift, 2011)
Background: Multimorbidity in the elderly often leads to inappropriate and harmful polypharmacy. Various approaches have been used to prioritize components of drug treatment, especially as on negative lists like the Beers list. A new approach is the FORTA assessments system (Fit fOR The Aged) in which drugs are graded as positive (A, should be given), intermediate (B or C), and negative (D should not be given). Methods: In this pilot study of 46 patients in a geriatric ward medication was assessed on admission and at discharge, using the FORTA criteria. All changes in the number of prescribed drugs, the distribution of FORTA criteria, and the number of drug interactions were recorded. Results: The use of FORTA resulted in a decrease in the total number of prescirbed drugs from 7.3 ± 2,9 to 6.7 ± 2,3 (p = 0.06), and an increase in positively assessed drugs (A / B) from 59 ± 20 to 77 ± 38% (p < 0.01), as well as a decrease in negatively assessed drugs (D) from 7 ± 12 to 5 ± 9% (p = 0.06). The number of drugs assessed as intermediate (C) did not change significantly. Under-treatment decreased from 65 to 39% (p < 0.01), over-treatment from 65% to 20% (p < 0.01). The number of drug interactions decreased from 79 to 54 (p < 0.01). Conclusion: This uncontrolled pilot study indicates that the FORTA criteria can be used in day-to-day clinical care: it describes the quality of changes in drug treatment in a geriatric ward in a plausible way. This study has provided basic uncontrolled data which should be validated in controlled studies comparing the quality of treatment with or without the use of the FORTA criteria.